The Danger Box - Balliett, Blue, 1955- (Scholastic Press, 2010)
In small-town Michigan, twelve-year-old Zoomy and his new friend Lorrol investigate the journal found inside a mysterious box and find family secrets and a more valuable treasure, while a dangerous stranger watches and waits.